NANOTECHNOLOGY APPLICATION IN COMPOSITE REBAR PRODUCTION - Gusev, Konstantin; Solovyev, Vladimir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The paper deals with the influence of metal/carbon nanocomposite additives on the physical properties of composite polymer reinforcement samples. Novel methods of composite rebar production have been suggested and tested. The overall positive effect of polymer composite material modification by selected additives has been found and analyzed.